From tradition to technology: a comprehensive review of contemporary food design - Xia, Bo; Zainal Abidin, Muhammad Rezza; Ab Karim, Shahrim (AZTI-Tecnalia, 2024)
Food design has long served as a means for restaurants to cater to the dietary preferences of their clientele. These designs, rooted in practicality, initially bear specific intentions from their creators, effectively acting as conduits through which chefs communicate messages to discerning palates. This comprehensive review aims to provide a meticulous exploration of the current landscape of food design, encompassing its connections to food culture and the multifaceted manifestations of processed food in terms of shapes, colors, and textures. The data draws from a substantial pool of 175 previous research articles, predominantly prioritizing high-quality sources to bolster the overall rigor of the review. Systematic organization of the literature was facilitated through Mendeley, with content analysis conducted via NVivo, and the integration of Sankey Diagrams to visualize data representation. This review unveils a compelling trend in the proliferation of food designs featuring 3D printing technology, marking a promising step forward in culinary innovation, with an increasing emphasis on the integration of artificial intelligence. This synthesis bridges the realms of food design and culinary aesthetics, forging new connections between established concepts and the latest frontiers in scientific inquiry. As the culinary world continues to evolve, this review positions itself as a significant literature contribution, offering valuable insights into the future of food design.